Characterization of Three SEPALLATA-Like MADS-Box Genes Associated With Floral Development in Paphiopedilum henryanum (Orchidaceae) - Cheng, Hao; Xie, Xiulan; Ren, Maozhi; Yang, Shuhua; Zhao, Xin; Mahna, Nasser; Liu, Yi; Xu, Yufeng; Xiang, Yukai; Chai, Hua; Zheng, Liang; Ge, Hong; et al. (Frontiers in Plant Science, 2022)
Paphiopedilum (Orchidaceae) is one of the world’s most popular orchids that is found in tropical and subtropical forests and has an enormous ornamental value. SEPALLATA-like (SEP-like) MADS-box genes are responsible for floral organ specification. In this study, three SEP-like MADS-box genes, PhSEP1, PhSEP2, and PhSEP3, were identified in Paphiopedilum henryanum. These genes were 732–916 bp, with conserved SEPI and SEPII motifs. Phylogenetic analysis revealed that PhSEP genes were evolutionarily closer to the core eudicot SEP3 lineage, whereas none of them belonged to core eudicot SEP1/2/4 clades. PhSEP genes displayed non-ubiquitous expression, which was detectable across all floral organs at all developmental stages of the flower buds. Furthermore, subcellular localization experiments revealed the localization of PhSEP proteins in the nucleus. Yeast two-hybrid assays revealed no self-activation of PhSEPs. The protein–protein interactions revealed that PhSEPs possibly interact with B-class DEFICIENS-like and E-class MADS-box proteins. Our study suggests that the three SEP-like genes may play key roles in flower development in P. henryanum, which will improve our understanding of the roles of the SEP-like MADS-box gene family and provide crucial insights into the mechanisms underlying floral development in orchids.